1996
DOI: 10.1101/gr.6.12.1185
|View full text |Cite
|
Sign up to set email alerts
|

Conserved linkage between the puffer fish (Fugu rubripes) and human genes for platelet-derived growth factor receptor and macrophage colony-stimulating factor receptor.

Abstract: We have cloned and sequenced the teleost homoiogs of the human genes encoding platelet-derived growth factor receptor-13 (PDGFRI3) and macrophage colony-stimulating factor I receptor (CSF1R) from the puffer fish Fugu rubripes. The Fugu PDGFRI3 and CSFIR genes each consist of 21 coding exons similar to the human CSFIR gene, but are considerably smaller than their human counterparts because of the smaller introns. Furthermore, the two Fugu genes are linked tandemly in a head-to-tail array similar to their human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
24
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 19 publications
(26 reference statements)
1
24
0
Order By: Relevance
“…Further studies will be required to con®rm these preliminary results, but this is consistent with several reports of conserved non-coding sequences, between Fugu and human genes, located in promoters, 3' UTR and even introns How et al, 1996;Kimura et al, 1997;Rowitch et al, 1998;Miles et al, 1998;Gellner and Brenner 1999). Some of them have been shown to have functional signi®cance in vivo Kimura et al, 1997;Rowitch et al, 1998).…”
supporting
confidence: 70%
“…Further studies will be required to con®rm these preliminary results, but this is consistent with several reports of conserved non-coding sequences, between Fugu and human genes, located in promoters, 3' UTR and even introns How et al, 1996;Kimura et al, 1997;Rowitch et al, 1998;Miles et al, 1998;Gellner and Brenner 1999). Some of them have been shown to have functional signi®cance in vivo Kimura et al, 1997;Rowitch et al, 1998).…”
supporting
confidence: 70%
“…Several additional examples where human/fugu comparisons led to putative gene regulatory elements are available (Abrahams et al 2002;Aparicio et al 1995;Bagheri-Fam et al 2001;Gilligan et al 2002;How et al 1996;Kimura et al 1997;Rowitch et al 1998;Venkatesh et al 1997). These studies highlight that a comparative genomic driven approach can be successful for identifying gene regulatory elements even in distant mammal/fish comparisons.…”
Section: Comparative Utility Of Non-mammalian Speciesmentioning
confidence: 99%
“…Similarly, studies of intergenic distances in Fugu also prove reduction to be the order of the day. How et al (1996) and Schofield et al (1997) have both examined tandemly arrayed genes that span large chromosomal regions in human and found substantial compaction in pufferfish. Aparicio et al (1997) showed that Fugu Hox gene clusters are compact by virtue of a combination of gene loss and reduction in intergenic distances.…”
mentioning
confidence: 99%